2022
DOI: 10.7759/cureus.21633
|View full text |Cite
|
Sign up to set email alerts
|

Working Towards Gender and Racial Diversity in Pediatric Residency Programs in the United States

Abstract: The gender and racial profile of the pediatric population in the United States (US) is more diverse than that of the pediatricians that cater to their healthcare needs. Gender and racial diversity remains limited among pediatric residents and fellows, faculty, and leadership. Our study objectives were to explore the gender and racial disparity among pediatric residents in the US. MethodsThis was a retrospective analysis of the Accreditation Council for Graduate Medical Education (ACGME) database. The database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 32 Additionally, it has been reported that female representation increased by 13.27% compared with +14.77% for men from 2007 to 2021, especially in pediatric residency programs. 33 Similarly, pediatricians in the US now comprise 63% women. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 Additionally, it has been reported that female representation increased by 13.27% compared with +14.77% for men from 2007 to 2021, especially in pediatric residency programs. 33 Similarly, pediatricians in the US now comprise 63% women. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with other surgical subspecialties, orthopedic surgery showed the lowest representation of racial minorities. 40 Additionally, Saboor et al 33 investigated the sex and racial and ethnic profiles of pediatric residents from 2011 to 2021. Those authors noted a large increase in the Asian (Pacific Islander) group by +58.42%, followed by Black (non-Hispanic) +45.24%, White (non-Hispanic) +43.37%, and Hispanic +42.18% groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation